Correlation Between Lipid Profile and Acne Vulgaris - Sobhan M; Seif Rabiei MA; Amerifar M (Dove Medical Press, 2020)
Mohammadreza Sobhan, 1 Mohammad Ali Seif Rabiei, 2 Maryam Amerifar 1 1Psoriasis Research Center, Department of Dermatology, Sina Hospital, Hamadan University of Medical Sciences, Hamadan, Iran; 2Department of Social Medicine, Hamadan University of Medical Sciences, Hamadan, IranCorrespondence: Mohammadreza SobhanPsoriasis Research Center, Department of Dermatology, Sina Hospital, Hamadan University of Medical Sciences, Mirzade Eshghy Street, Hamadan 65168408741, IranTel +989121089455Fax +988138269808Email mreza_sobhan@yahoo.comBackground and Aim: Acne is a common skin disease resulting from a complex interaction of various pathogenetic factors. The aim of this study was to find out lipid profile abnormalities in acne vulgaris patients.Material and Methods: This descriptive analytic cross-sectional study was conducted on 45 acne patients and 45 age- and sex-matched healthy controls to assess plasma total cholesterol (TC), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels.Results: We showed a higher cholesterol level in acne patients (P=0.025), particularly in men (P=0.04). Other plasma lipids including TG, LDL, and HDL in male and female patients were higher compared to controls, but this is not statistically significant.Discussion and Conclusion: In conclusion, lipid profile was altered in our patients, with high cholesterol level as the commonest derangement, particularly in men. Therefore, screening for lipid profile abnormalities could be considered in the treatment of acne patients.Keywords: acne vulgaris, lipid profile, severity